Pemanfaatan Limbah Bauksit (Tailing Bauxite) Sebagai Bahan Pengganti Agregat Halus Terhadap Kuat Tekan, Kuat Tarik Belah, dan Modulus Elastisitas Pada Beton - Rabihati, Etty; Purnama, Ikhwan Arief; Adjie, Muhammad Syafri; Rachmawan, Valdi Dwi (Jurusan Teknik Sipil Polnep, 2020)
Until now, bauxite waste (bauxite tailings) has not been utilized in its entirety, causing an increase in the amount of waste in the bauxite producing areas. The percentage between the bauxite produced and the amount of waste produced is 50%: 50%. This research was conducted to see whether or not the use of liquid waste (tailings bauxite) is appropriate as a place for fine aggregate in the manufacture of concrete. This study used an experimental method with the replacement of the concrete mixture, namely sand with bauxite waste (bauxite tailings) with the proportion of bauxite waste (bauxite tailings) of 2.5%, 5%, and 7.5%. The tests carried out were compressive strength testing, split tensile strength testing, and modulus of elasticity. The results of the test for the highest compressive strength average age of 7 days were found in normal concrete with an average compressive strength of 21.58 MPa. The average compressive strength of 28 days was 7.5% bauxite waste concrete with an average compressive strength of 32.07 MPa. The tensile strength of 7 days was in bauxite waste concrete at 7.5% with a split tensile strength of 2.90 Mpa. The tensile strength of 28 days was in bauxite waste concrete 7.5% with a split tensile strength of 3.26 Mpa. The highest average modulus of elasticity is found in 7.5% bauxite waste concrete with a yield of 26607.03 Mpa, Keywords: Bauxite Waste (Tailing Bauxite), Compressive Strength, Modulus of Elasticity, Split Tensile Strength